2020
DOI: 10.1097/ccm.0000000000004290
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in Pediatric Critical Care Medicine Fellows*

Abstract: Objectives: Assess the overall level of burnout in pediatric critical care medicine fellows and examine factors that may contribute to or protect against its development. Design: Cross-sectional observational study. Setting: Accreditation Council for Graduate Medical Education-accredited pediatric critical care medicine fellowship programs across the United States. Subjects:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…Burnout was assessed using the Maslach Burnout Inventory‐General Survey (MBI‐GS), a validated version for measuring burnout in HCWs (Suttle et al, 2020; Wu et al, 2020). This instrument encompasses emotional exhaustion (tiredness, somatic symptoms, and decreased emotional resources), depersonalization (developing negative, cynical attitudes, and impersonal feelings), and reduced personal accomplishment (feelings of incompetence, inefficiency, and inadequacy) (Kumar, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Burnout was assessed using the Maslach Burnout Inventory‐General Survey (MBI‐GS), a validated version for measuring burnout in HCWs (Suttle et al, 2020; Wu et al, 2020). This instrument encompasses emotional exhaustion (tiredness, somatic symptoms, and decreased emotional resources), depersonalization (developing negative, cynical attitudes, and impersonal feelings), and reduced personal accomplishment (feelings of incompetence, inefficiency, and inadequacy) (Kumar, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…At the start of their training, pediatric cardiology fellows at a single institution self-reported fears and stressors [ 22 ]. Pediatric emergency medicine and critical care fellows across the country self-reported stressors, and identified factors associated with burnout using Likert scales [ 5 , 23 ]. The findings in these studies were similar to ours: fellows identified stressors including mental illness and burnout, finances, underrepresented group discrimination, especially based on gender, work-life balance, unusual work schedule, high work load and expectations, negative work environment, and lack of confidence and feelings of inadequacy.…”
Section: Discussionmentioning
confidence: 99%
“…No studies have identified self-reported stressors for pediatric residents; they have only been identified by program directors [ 19 ] or by collecting objective data such as work hours and demographics and comparing them to burnout data [ 4 , 20 , 21 ]. Only a few studies have queried pediatric subspecialty fellows about their stressors [ 5 , 22 , 23 ], but all of these studies focused on specific subspecialties rather than pediatric fellows more generally.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously seen that schedule flexibility reduces clinician burnout. 9 While clinical responsibilities rarely afford this freedom, the asynchronous opportunity provided by VL may be an invaluable resource to give providers flexibility for conference and didactic review at their own pace. The present study did not account for additional asynchronous attendance from those who later watched recordings.…”
Section: Discussionmentioning
confidence: 99%